Experimental investigation on the factors affecting the quality of titanium alloy overhang via selective laser melting forming - Su, Chunjian (2023)
Selective laser melting (SLM) technology has attracted wide attention because it can produce parts with complex shape or internal characteristics that are difficult to process in traditional ways. SLM process is very easy to produce dross formation and balling defects on the overhanging surface of titanium alloy when forming the overhanging characteristic structural parts, which makes the surface of the formed parts rough. Therefore, how to improve the forming quality of titanium alloy overhanging parts by adding material becomes an urgent problem to be solved. In this paper, the influence factors and mechanism of quality of titanium alloy suspension parts formed by SLM process are experimentally studied. Through analysis and comparison of forming parts under different geometric dimensions and process parameters, appropriate geometric dimensions and process parameters are obtained to improve the quality of forming parts. In terms of scanning strategy, a compound scanning path of “vertical island zoning + contour remelting” is put forward to solve the problems of stress concentration and dross formation on the overhanging surface. This strategy is based on vertical island zoning and improves the heat dissipation at the edge of the part by remelting the contour of the formed layer. The result shows that this method can effectively reduce the residual stress of the overhanging part and improve the dross formation phenomenon.